Theoretical Study on Formamide (NH2CHO) and Methylidene (CH2) Reactions for the Formation of Interstellar N-Methylformamide - Shivani; Ahamad, Aftab; Singh, Manisha; Singh, Keshav; Misra, Alka; Tandon, Poonam (Organic Chemistry Plus, 2022)
N-methylformamide (NMF), E & Z containing an amide bond, a vital component of peptides, is one of the simplest derivatives of formamides. It is detected towards the hot molecular core of the Sgr B2(N2) molecular cloud with the Atacama Large Millimeter/submillimeter Array (ALMA). It is proposed that the radical-molecule mechanism can be used as a strong contrivance to investigate the formation of NMF in the interstellar medium (ISM) via some interstellar molecules like methylidene CH2(1Σ1 & 3Σ1) and formamide (NH2CHO). The density functional theory (DFT) at B3LYP/6-311G (d,p) has been applied to study the mechanisms. All the possible cases of E- & Z-NMF formation with singlet and triplet CH2 have been investigated. It is found that the formation of E-NMF with CH2(1Σ1) and Z-NMF with CH2(3Σ1) is more feasible and favorable in comparison to E-NMF formation from CH2(3Σ1) and Z-NMF with CH2(1Σ1).